2015
DOI: 10.1371/journal.pone.0137027
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and MicroRNA Expression Analysis in Small Arteries of Spontaneously Hypertensive Rats. Evidence for ER Stress

Abstract: Small arteries are known to develop functional and structural alterations in hypertension. However, the mechanisms of this remodeling are not fully understood. We hypothesized that altered gene expression is associated with the development of hypertension in mesenteric arteries of spontaneously hypertensive rats (SHR). Three sublines of SHR and normotensive Wistar Kyoto rats (WKY) were studied at 6 weeks and 5 months of age. MiRNA and mRNA microarray experiments were performed and analyzed with bioinformatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Likewise, vascular ER stress is present in spontaneously hypertensive rats and is accompanied by elevations in endothelium‐dependent contraction and myogenic constriction, as well as reductions in endothelium‐dependent vasodilatation (Palao et al . ; Carlisle et al . ; Choi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, vascular ER stress is present in spontaneously hypertensive rats and is accompanied by elevations in endothelium‐dependent contraction and myogenic constriction, as well as reductions in endothelium‐dependent vasodilatation (Palao et al . ; Carlisle et al . ; Choi et al .…”
Section: Introductionmentioning
confidence: 99%
“…The ER stress response has indeed been linked to vascular dysfunction (8), and induction of ER stress increases the blood pressure and impairs the endothelial dependent relaxation in aorta of normotensive rats (18). In addition, in our previous study in mesenteric arteries of spontaneously hypertensive rats, we found that TSP-4, Atf6α and the ER stress response genes were significantly upregulated (16). Thus, we speculate that the impaired relaxation hypertension depends on the role of TSP-4 in ER stress.…”
Section: Small Artery Functionmentioning
confidence: 64%
“…For this purpose, wild-type and Thbs4 knockout mice were treated with Ang II to reach a hypertensive state. We analyzed several cardiovascular parameters, but focused on small arteries, where we previously identified a sizeable increase in Thbs4 expression (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the authors proposed that the conserved type 3 repeats of TSPs have a critical intracellular role in ER stress response by driving Atf6α‐dependent enhancement of protein secretion, to promote reconstruction of the ECM after injury. More recently, correlated upregulated expression of Thbs4 and Atf6‐target genes has been identified in vivo, in mesenteric arteries of the spontaneously hypertensive rat .…”
Section: Intracellular Localisation and Roles — Evidence Of Mechanismsmentioning
confidence: 99%